2004
DOI: 10.1021/es034742e
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Bioavailability and Accumulation in the Presence of Humic Acid to the Zebra Mussel, Dreissena polymorpha

Abstract: Metal speciation in aquatic systems is mainly determined by the type and concentration of ligands present in solution. A very important group of complexing agents is dissolved organic matter (DOM), e.g., humic and fulvic acids. According to the free-ion activity model, only the free metal ion is available to biota. Nevertheless, DOM has been reported to decrease or increase metal uptake, leading to uncertainty concerning the bioavailability of metal-DOM complexes. In this work the effect of Aldrich humic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 37 publications
2
27
0
2
Order By: Relevance
“…The effects of DOM on Cd bioaccumulation in D. polymorpha observed in the present study are consistent with apparently contradictory results obtained by Voets et al [10] and Roditi et al [14]. Voets et al [10] found that the presence of approximately 55 mg/L (i.e., $23 mgDOC/L) of Aldrich humic acid in the medium prevented Cd accumulation, whereas Roditi et al [14] showed that a small amount of DOC (concentrations of DOC derived from algae ranged from 1.96 to 3.28 mg/L) enhanced metal uptake.…”
Section: Influence Of Dom On CD Bioaccumulationsupporting
confidence: 92%
See 1 more Smart Citation
“…The effects of DOM on Cd bioaccumulation in D. polymorpha observed in the present study are consistent with apparently contradictory results obtained by Voets et al [10] and Roditi et al [14]. Voets et al [10] found that the presence of approximately 55 mg/L (i.e., $23 mgDOC/L) of Aldrich humic acid in the medium prevented Cd accumulation, whereas Roditi et al [14] showed that a small amount of DOC (concentrations of DOC derived from algae ranged from 1.96 to 3.28 mg/L) enhanced metal uptake.…”
Section: Influence Of Dom On CD Bioaccumulationsupporting
confidence: 92%
“…It was also demonstrated that Zn had a protective effect on Cd toxicity [8,9]. The protective effect of dissolved organic matter (DOM) has been reported by different studies [10,11], because it modifies Cd speciation. However, some exceptions were also reported, in particular for some bivalves like Mytilus edulis or Dreissena polymorpha [12][13][14].…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, the uptake of some allochthonous materials by veligers cannot be ruled out. Adult zebra mussels are known to take up humic acids in addition to algal lysates (Voets et al 2004), but the d 13 C of humics is likely to reflect their terrestrial origins and the nonterrestrial signature of zebra mussel veligers in the St. Lawrence River implies that this is not a primary source in their diet.…”
Section: Discussionmentioning
confidence: 99%
“…When truly dissolved, uptake of Cd can be a result of diffusion through respiratory surfaces and the epidermis, whereas when it is associated with dissolved (DOM) and particulate (POM) organic matter, the exposure is presumably higher through the diet (Wang and Fisher, 1999;Lee et al, 2000). However, when associated with DOM, the bioavailability of Cd may be limited (Voets et al, 2004). The speciation and bioavailability of metals also varies with chemical conditions in the sediment, such as pH (Heijerick et al, 2003), salinity and redox potential.…”
Section: Bioaccumulation Of Cadmiummentioning
confidence: 99%